Development of an Internet of Things (IoT)-Based Teacher Performance Evaluation System to Improve the Quality of Basic Education - Etiyasningsih, Etiyasningsih; Sundari, Sri; Zulinar, Ariel Teta; Sagiokta, Wahyu Ivana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to integrate the Internet of Things (IoT) in teacher performance evaluation in elementary schools to improve efficiency, accuracy, and transparency in assessment. The method used in this study is a mixed approach, which involves collecting data through questionnaires, interviews, and observations. The results of the study show that YIMI Gresik Elementary School is ready to adopt IoT with various devices that support real-time data collection. IoT-based evaluation systems are able to increase objectivity and transparency in teacher performance assessments, as well as accelerate feedback provided to teachers. The study also found that the application of IoT can reduce the subjectivity that often arises in manual evaluations and improve the quality of teaching through more efficient systems. The implications of this study show that the integration of IoT in the evaluation system can optimize education management, especially in improving the quality of teacher performance evaluation. However, the challenges faced, such as inadequate infrastructure and the need for more intensive training, must be addressed immediately in order for the implementation of IoT to run effectively across primary schools. Follow-up research is expected to examine the long-term impact of the use of IoT-based evaluation systems on teaching quality and student learning outcomes.